Endogenous heterogeneous gender norms and the distribution of paid and unpaid work in an intra-household bargaining model - Theresa Hager; Patrick Mellacher; Magdalena Rath (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2023)
We study the impact of gender norms on the distribution of paid and unpaid labor between women and men in an intra-household bargaining model featuring endogenous social norms. In contrast to the previous literature, which assumes a homogeneous social norm, agents are connected via explicitly modeled social networks and accordingly face heterogeneous perceptions of gender norms. In our model, social pressure to conform to gender norms exacerbates gender inequalities in the distribution of paid and unpaid labor that may result from a gender pay gap or gender-specific preferences. However, we show that the behavior of agents connected in different standardized social networks is significantly closer to a situation in which agents face no social pressure than in a scenario in which the whole of society perceives homogeneous gender norms. This is particularly true if agents are more likely to form connections to other agents that have similar preferences.
Keywords: C63; C78; D13; J16; J22; 330; intra-household bargaining; social norms; agent-based model; social network